A School Partnership Model for Improving Children's Learning Achievement in Special Schools - Reja Ribretin Milala; Elianasari; Kamaludin; Syafaat Ariful Huda (Didaktika: Jurnal Kependidikan, 2026)
Partnerships between schools and parents are an important factor in the educational success of children with special needs (CSN), particularly in special schools. This study aims to describe the model of school and parent partnership in improving the learning achievements of CSN at SLB Negeri 7 Jakarta. The approach used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study show three main partnership models, namely: communicative partnership, participatory partnership, and collaborative partnership, carried out through the preparation and implementation of the Individualized Education Program (IEP). Supporting factors for the partnership include participative school leadership, opencommunication, and increased parental awareness.